2007
DOI: 10.1507/endocrj.k05-157
|View full text |Cite
|
Sign up to set email alerts
|

Medical Treatment of Benign Insulinoma Using Octreotide LAR: A Case Report

Abstract: Abstract. In some patients with insulinoma, surgery is not possible due to either difficulties in detecting the tumor or advanced age. These patients need medical treatment for hypoglycemia. We report a case of benign insulinoma using the long-acting octreotide formulation, octreotide long-acting repeatable (octreotide LAR), as a medical therapy. A 67-yearold woman was referred to our hospital for examinations of hypoglycemia. A blood sample taken during a hypoglycemic episode revealed low plasma glucose conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 17 publications
2
15
0
2
Order By: Relevance
“…Pharmacological treatment with diazoxide, octreotide, and calcium channel blockers has been tried in patients with insulinoma who fail to respond to surgical treatment or those who have contraindications to surgery [9][10][11]. In patients with reactive hypoglycemia, alfa-glicosidase inhibitors, particularly acarbose, have also been used [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological treatment with diazoxide, octreotide, and calcium channel blockers has been tried in patients with insulinoma who fail to respond to surgical treatment or those who have contraindications to surgery [9][10][11]. In patients with reactive hypoglycemia, alfa-glicosidase inhibitors, particularly acarbose, have also been used [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Although this association is interesting, it is unclear whether there is a positive correlation between SSTR2 expression and glucose-stimulated insulin secretion. Additionally, since it has been reported that octreotide was effective in elderly patients with insulinoma [10,19,20], the relationship between SSTR2 expression and age is interesting. However, it is also unclear whether SSTR2 expression is correlated to age in our results.…”
Section: Discussionmentioning
confidence: 99%
“…Das Nüchterninsulin im Serum beträgt 36,4 μE/ml (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) und das C-Peptid 4,68 ng/ml (0,78-1,89) bei einem Glucosewert von 37 mg/dl. Auf einen Fastentest wird aufgrund der niedrigen Nüchtern-blutzuckerwerte verzichtet.…”
Section: Diagnostik Laborbefundeunclassified
“…Auch die in der Literatur oft als effektiv beschriebene Gabe von Somatostatinanaloga [10,13] erwies sich trotz des Nachweises von Somatostatinrezeptoren im Tumorgewebe nicht als effektiv, wenngleich natürlich noch weitere Dosissteigerungen möglich gewesen wären. Auf einen Behandlungsversuch mit Diazoxid, einer Substanz, die die Insulinsekretion reversibel verringert, haben wir in Anbetracht der möglichen Natriumretention und Ödemneigung verzichtet und einen chirurgischen Ansatz gewählt.…”
Section: Therapieunclassified